Intracolonial demography, biomass and food consumption of Macrotermes natalensis (Haviland) (Isoptera: Termitidae) colonies in the northern Kruger National Park, South Africa - Crewe, Robin M. (University of Pretoria, 2013)
Dissertation (PhD)--University of Pretoria, 2003.